2017
DOI: 10.1176/appi.ajp.2016.15111410
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Error Representation in Individuals With Generalized Anxiety Disorder During Passive Avoidance

Abstract: Objective Deficits in reinforcement-based decision-making have been reported in Generalized Anxiety Disorder. However, the pathophysiology of these deficits is largely unknown, extant studies have mainly examined youth and the integrity of core functional processes underpinning decision-making remain undetermined. In particular, it is unclear whether the representation of reinforcement prediction error (PE: the difference between received and expected reinforcement) is disrupted in Generalized Anxiety Disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 30 publications
(46 reference statements)
7
53
2
Order By: Relevance
“…We hypothesized that for both approached and avoided stimuli, children with maltreatment experience would show reduced modulation of blood oxygen level dependent (BOLD) responses by EV in four regions of interest (ROIs): the DS and VS striatum, the medial OFC (mOFC), and the lateral OFC (lOFC). As noted earlier, this is in line with evidence from studies of reinforcement expectancies representation in those psychiatric disorders associated with maltreatment, with the animal literature of early adversity, and with some preliminary evidence from studies of extreme neglect (e.g., Forbes et al, 2009;Mehta et al, 2010;Smoski et al, 2011;Stringaris et al, 2015;White et al, 2013White et al, , 2017. In addition, consistent with substantial evidence of increased neural activation to negative stimuli and negative feedback among abused and neglected children (e.g., Lim et al, 2015;McCrory et al, 2011;McLaughlin et al, 2015), we hypothesized that children with maltreatment experience would show increased modulation of BOLD responses by PE during punishment feedback in four ROIs: the amygdala, the insula, and the anterior cingulate cortex (ACC) and midcingulate cortex (MCC).…”
Section: Hypothesessupporting
confidence: 83%
“…We hypothesized that for both approached and avoided stimuli, children with maltreatment experience would show reduced modulation of blood oxygen level dependent (BOLD) responses by EV in four regions of interest (ROIs): the DS and VS striatum, the medial OFC (mOFC), and the lateral OFC (lOFC). As noted earlier, this is in line with evidence from studies of reinforcement expectancies representation in those psychiatric disorders associated with maltreatment, with the animal literature of early adversity, and with some preliminary evidence from studies of extreme neglect (e.g., Forbes et al, 2009;Mehta et al, 2010;Smoski et al, 2011;Stringaris et al, 2015;White et al, 2013White et al, , 2017. In addition, consistent with substantial evidence of increased neural activation to negative stimuli and negative feedback among abused and neglected children (e.g., Lim et al, 2015;McCrory et al, 2011;McLaughlin et al, 2015), we hypothesized that children with maltreatment experience would show increased modulation of BOLD responses by PE during punishment feedback in four ROIs: the amygdala, the insula, and the anterior cingulate cortex (ACC) and midcingulate cortex (MCC).…”
Section: Hypothesessupporting
confidence: 83%
“…) and anxiety (Hartley & Phelps, ; White et al. ). A recent longitudinal fMRI study with a large community sample of adolescents ( n = 1576) has reported that blunted striatal response during the anticipation of rewards predicts future clinical status and anhedonia in a dose‐dependent fashion (Stringaris et al., ).…”
Section: Functional Magnetic Resonance Imaging and The Study Of Childmentioning
confidence: 99%
“…In addition, inferior frontal gyrus/anterior insula cortex (iFG/aIC), dorsal anterior cingulate cortex (dACC) and striatum have been implicated in the avoidance of sub-optimal choices (Budhani et al, 2007; Casey et al, 2001) as a function of EV (Kuhnen and Knutson, 2005; Liu et al, 2007). Failure to represent EV or PE have been associated with decision-making deficits in a number of disorders, including Parkinson’s Disease (Averbeck et al, 2013), conduct disorder (White et al, 2014, 2013), depression (Kumar et al, 2008) and generalized anxiety disorder (White et al, in press). …”
Section: Introductionmentioning
confidence: 99%